2022
DOI: 10.1002/ctd2.42
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between emerging models and humans by learning from polio animal studies: A systematic review

Abstract: Disease modelling plays a fundamental role in biomedical research, even more in virology where the virus depends strictly on its host for replication. Although animal models are extensively used in virology, there is an increasing demand for animal‐free research. Therefore, during this transition, it is crucial to learn and take advantage of animal research to better implement new emerging models. In this study, we aim to systematically review the translation from animal models to humans for the well‐character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…It has been reported that chick embryo cells or hamster embryo cells previously exposed to poliovirus type 1 and then exposed to irradiated Sendai virus as a fusion inducing agent (which induce cell fusion and multinucleated giant cells), leads to the replication of poliovirus ( 165 ). Murine cells can become susceptible to poliovirus infection after they have been transfected with a DNA construct expressing the human CD155 receptor ( 166 , 167 ). Infected cells show cytopathic effects within 4 to 6 h, and release up to 10,000 newly infectious virus particles upon cell lysis.…”
Section: Interspecies Circulation Of Poliovirusesmentioning
confidence: 99%
“…It has been reported that chick embryo cells or hamster embryo cells previously exposed to poliovirus type 1 and then exposed to irradiated Sendai virus as a fusion inducing agent (which induce cell fusion and multinucleated giant cells), leads to the replication of poliovirus ( 165 ). Murine cells can become susceptible to poliovirus infection after they have been transfected with a DNA construct expressing the human CD155 receptor ( 166 , 167 ). Infected cells show cytopathic effects within 4 to 6 h, and release up to 10,000 newly infectious virus particles upon cell lysis.…”
Section: Interspecies Circulation Of Poliovirusesmentioning
confidence: 99%
“…Although these studies have greatly facilitated our understanding of the virus replication cycle in vitro, these models do not fully recapitulate the complexity of the human gastrointestinal epithelium with its multiple cell types [ 12 ]. Because cell lines constitute a single cell type, these models are limited and often fail to provide a reliable understanding of viral pathogenesis in humans [ 13 ]. In addition, the lack of a reliable in vitro, or ex vivo, model has hindered the research on novel antiviral treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These hard-to-grow viruses are predominantly present in Africa, and they spread mainly among children [ 18 , 19 ]. Based on the studies on poliovirus [ 20 , 21 , 22 ] and other EV [ 23 , 24 ], the primary replication sites of EV-C are believed to be the gastrointestinal and respiratory epithelium. CVA-1, CVA-13, CVA-15, and CVA-17 to CVA-22, EV-C96, and EV-C99 are considered gastrointestinal EV-C as they are mainly isolated from the stool samples in cases of mild to severe gastrointestinal symptoms [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%